2016
DOI: 10.1016/j.combustflame.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Compositional effects on the ignition of FACE gasolines

Abstract: As regulatory measures for improved fuel economy and decreased emissions are pushing gasoline engine combustion technologies towards extreme conditions (i.e., boosted and intercooled intake with exhaust gas recirculation), fuel ignition characteristics become increasingly important for enabling stable operation. This study explores the effects of chemical composition on the fundamental ignition behavior of gasoline fuels. Two well-characterized, high-octane, non-oxygenated FACE (Fuels for Advanced Combustion E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
239
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(251 citation statements)
references
References 86 publications
(114 reference statements)
9
239
3
Order By: Relevance
“…It was also shown that these discrepancies in IDT at low temperatures can result in significant differences in the combustion phasing of a CI engine operating at low loads [28,34]. [29], FACE A & C from [35], HSRN from [28], GCI blend from this work.…”
Section: Fig 1 Measured Ignition Delay Times Of the Gci Blend And Tmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also shown that these discrepancies in IDT at low temperatures can result in significant differences in the combustion phasing of a CI engine operating at low loads [28,34]. [29], FACE A & C from [35], HSRN from [28], GCI blend from this work.…”
Section: Fig 1 Measured Ignition Delay Times Of the Gci Blend And Tmentioning
confidence: 99%
“…Even though molecular structure is a very important indicator of the fuel reactivity, matching the molecular structure of all components of the real fuel can be challenging and can lead to a relatively large surrogate mixture [29] for which detailed or reduced chemical kinetic models may not be available. Computational cost will also be high for surrogates containing too many components.…”
Section: Fuel Characterization and Surrogate Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 4-component surrogates involving TRF/1-pentene and TRF/2-pentene have also been formulated and investigated by e.g. [14][15][16], as well as complex multicomponent surrogates for various non-oxygenated gasolines [17,18]. The reasonable extent of agreement between TRF and gasoline, in addition to the availability of well validated chemical mechanisms of its oxidation pathways, makes it currently a more feasible surrogate for gasoline in terms of ignition delay modelling compared to more complex surrogates [19] and blending effects, and hence it is used in this work.…”
Section: Surrogate Formulationmentioning
confidence: 99%